2008
DOI: 10.30970/cma1.0050
|View full text |Cite
|
Sign up to set email alerts
|

The competition between InBi- and In2Bi-like atomic distributions before solidification

Abstract: The enthalpy of mixing of binary In-Bi melts was measured by means of a calorimetric method at T = 1023, 875, 483 K. Its concentration dependence reveals a flat minimum in the region between the intermetallic phases InBi and In 2 Bi. The shape of the curve of the integral enthalpy of mixing for liquid In-Bi alloys is in agreement with the assumption of a competition between InBi-and In 2 Bi-like chemical ordering before solidification. Enthalpy of mixing / In-Bi molten alloys / Intermetallic phase / Associate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
1
1
0
Order By: Relevance
“…These complex structural transformations of liquid InBi compound at heating are consistent with previously published conclusions about the thermodynamic features of In-Bi alloys [33,34]. In particular, these studies concluded about the existence of clusters of stoichiometric composition corresponding to InBi and In 2 Bi compounds that coexist in the melt just upon melting.…”
Section: Resultssupporting
confidence: 91%
“…These complex structural transformations of liquid InBi compound at heating are consistent with previously published conclusions about the thermodynamic features of In-Bi alloys [33,34]. In particular, these studies concluded about the existence of clusters of stoichiometric composition corresponding to InBi and In 2 Bi compounds that coexist in the melt just upon melting.…”
Section: Resultssupporting
confidence: 91%
“…Where P AA and P BB are respectively zero for µ < 2 and ν < 2 . Using equations ( 5), ( 6), (7), equation ( 4) can be written as…”
Section: Thermodynamic Propertiesmentioning
confidence: 99%